Tobacco screening and cessation efforts by dental providers: A quality measure evaluation. (19th December 2018) - Neumann, Ana; Kumar, Shwetha; Bangar, Suhasini; Kookal, Krishna Kumar; Spallek, Heiko; Tokede, Oluwabunmi; Simmons, Kristen; Even, Joshua; Mullins, Joanna; Mertz, Elizabeth; Yansane, Alfa; Obadan‐Udoh, Enihomo; et al.
Abstract: Objectives: The purpose of this study was to adapt, test, and evaluate the implementation of a primary care "Preventive care and Screening" meaningful use quality measure for tobacco use, in dental institutions. We determined the percentage of dental patients screened for tobacco use, and the percentage of tobacco users who received cessation counseling. Methods: We implemented the dental quality measure (DQM), in three dental schools and a large dental accountable care organization. An automated electronic health record (EHR) query identified patients 18 years and older who were screened for tobacco use one or more times within 24 months, and who received cessation counseling intervention if identified as a tobacco user. We evaluated EHR query performance with a manual review of a subsample of charts. Results: Across all four sites, in the reporting calendar year of 2015, a total of 143, 675 patients met the inclusion criteria for the study. Within 24 months, including 2014 and 2015 calendar years, percentages of tobacco screening ranged from 79.7 to 99.9 percent, while cessation intervention percentages varied from 1 to 81 percent among sites. By employing DQM research methodology, we identified intervention gaps in clinical practice. Conclusions: We demonstrated the successful implementation of a DQM to evaluate screening rates for tobacco use and cessation intervention. There is substantial variation in the cessation intervention rates across sites, and these results are a call for action for the dental profession to employ tobacco evidence‐based cessation strategies to improve oral health and general health outcomes.